Phytochemical components and biological activities of Silene arenarioides Desf. Issue 23 (2nd December 2017) - Golea, Lynda; Benkhaled, Mohammed; Lavaud, Catherine; Long, Christophe; Haba, Hamada
Abstract: In this study, six known compounds1 –6 were isolated from the aerial parts of Silene arenarioides Desf . using different chromatographic methods. The structures of these compounds were identified as maltol glycoside (1 ), soyacerebroside I (2 ), chrysin (3 ), apigenin (4 ), quercetin (5 ) and stigmasterol glucoside (6 ). The compounds (1 ) and (2 ) are reported for the first time from this genus. The isolated compounds were determined using NMR techniques ( 1 H NMR, 13 C NMR, COSY, HSQC and HMBC) and mass spectroscopy (ESI-MS). The antibacterial and antioxidant activities of extracts and of compound (1 ) have been evaluated. The antioxidant activity was performed by DPPH radical scavenging method, which showed that methanol extract possesses a good antioxidant activity with value of IC50 = 8.064 ± 0.005 μg/mL. Abstract :